2022
DOI: 10.3390/antibiotics11060748
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Use, Incidence and Risk Factors for Orthopedic Surgical Site Infections in a Teaching Hospital in Madhya Pradesh, India

Abstract: Orthopedic surgeries contribute to the overall surgical site infection (SSI) events worldwide. In India, SSI rates vary considerably (1.6–38%); however, there is a lack of a national SSI surveillance system. This study aims to identify the SSI incidence, risk factors, antibiotic prescription and susceptibility patterns among operated orthopedic patients in a teaching hospital in India. Data for 1205 patients were collected from 2013 to 2016. SSIs were identified based on the European Centre for Disease Prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…This has also been seen in the literature. It shows that male sex is a significant risk factor for SSIs [6,11]. Most of the SSIs are related to lower limb surgeries which can also be observed in other studies [10].…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This has also been seen in the literature. It shows that male sex is a significant risk factor for SSIs [6,11]. Most of the SSIs are related to lower limb surgeries which can also be observed in other studies [10].…”
Section: Discussionsupporting
confidence: 69%
“…In a study conducted in an orthopaedic centre in the United States, the incidence was 2.55% [10]. Another Indian study among 1205 orthopaedic patients showed an incidence of 7.6% [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In abdominal surgery, the antibiotics often given are cefotaxime, metronidazole, cefradine, and amoxicillin/clavulanate. In orthopedic surgery, the antibiotic often prescribed is amikacin [23].…”
Section: Figure 1 Number Of Publications By Yearmentioning
confidence: 99%